Energy Efficiency in Russia : Untapped Reserves - International Finance Corporation (Washington, DC, 2014)
This report was designed to provide senior Russian policymakers with a comprehensive and practical analysis of energy efficiency in Russia: potential, benefits, and recommendations on how to fully tap into this resource. Shortly after his inauguration, President Medvedev made several public statements identifying Russia s inefficient use of energy, and the associated economic and ecological consequences, as one of the most pressing problems facing the nation. He has called for an action plan to halve Russia s energy intensity by 2020. The goal of this report is to make a significant contribution toward developing such a plan.